Nonlinear behavior of TiO2 center dot Ta2O5 center dot MnO2 material doped with BaO and Bi2O3 - Bomio, MRD; Sousa, V. C.; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2004)
A study was made on the effect of the addition of BaO (0.025-0.05 mol%) and Bi2O3 (0.025-0.05 mol%) to the TiO2.Ta2O5.MnO2 material. The samples were characterized by X-ray diffraction, and current-voltage measurements were accomplished for determination of the nonlinear coefficient. An analysis was made to evaluate the microstructural characteristics of the materials. The most appropriate sintering conditions for the materials were analyzed with the purpose of obtaining the best nonlinear coefficient associated with the smallest breakdown electric field. After sintering at 1400 degreesC for 2 h, a low-voltage (30 V cm(-1)) varistor was obtained, which, however, presented a low nonlinear coefficient (6). It was found that the sintering conditions must be controlled in order to improve the electrical properties of these materials. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: TiO2; Ta2O5; MnO2; varistors; electrical ceramics